2019
DOI: 10.1007/s10329-019-00721-4
|View full text |Cite
|
Sign up to set email alerts
|

Social attention biases in juvenile wild vervet monkeys: implications for socialisation and social learning processes

Abstract: We are grateful to the late K. van der Walt for permission to conduct the study in his reserve. The authors would like to thank especially M. Bodin for collecting the focal data in one of the groups (NH), in addition of the other students and volunteers for their assistance in long term data collection at IVP, and the on-site manager A. van Blerk, for his great support. We thank A. Whiten for his useful comments on the manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 98 publications
0
20
0
3
Order By: Relevance
“…Yet, in mandrills and the rhesus macaque females in our study such an effect of subject rank on attention for agonism and affiliation of others was not found to go above and beyond the relative effects described above 13 . This discrepancy may be explained by rank dependent differences in the time course of gazing 16 that cannot be picked up with the methods employed in the latter studies (but see 14 ). The methods employed here do not allow discerning which of the interaction partners the subject was gazing at.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Yet, in mandrills and the rhesus macaque females in our study such an effect of subject rank on attention for agonism and affiliation of others was not found to go above and beyond the relative effects described above 13 . This discrepancy may be explained by rank dependent differences in the time course of gazing 16 that cannot be picked up with the methods employed in the latter studies (but see 14 ). The methods employed here do not allow discerning which of the interaction partners the subject was gazing at.…”
Section: Discussionmentioning
confidence: 90%
“…Like any visual monitoring it may also attract the attention of those observed with possible negative effects like redirected aggression. The upside is that social monitoring may also facilitate social learning which may be particularly important for immatures 14 . Future studies will explore the immediate consequences of social monitoring.…”
Section: Scientific Reports |mentioning
confidence: 99%
“…An individual might be copied more than other potential demonstrators because it performs the behavior more (performance bias), and/or because its actions are more likely to be observed than the actions of others (attention bias). For example, Older and higher-ranking capuchins have been found to be more frequently watched by conspecifics while cracking nuts 30 ; vervet monkeys have been reported to show a greater attention to female models 25 but not to dominants 27,31 , and juveniles have been reported to pay more attention to their maternal relatives when foraging 31 . The performance and attention bias effects multiplied together determine the rate at which an individual is observed.…”
mentioning
confidence: 99%
“…Statistical techniques applied to social network analysis have greatly evolved in the last 10 years (Hoppitt and Laland 2013;Farine 2017;Finn et al 2017;Sosa 2018). Papers in this issue show that whilst it is commonly accepted now to use permutation tests to avoid interdependence of social data (Koyama and Aureli 2018; Kawazoe and Sosa 2018, Rodrigues and Boeving 2018), new tools have emerged to study the social positions of individuals inside their network (i.e., egocentric network; Grampp et al 2019), the multidimensional nature of networks (i.e., multiplex networks; Smith-Aguilar et al 2018) and their dynamics (e.g., through ERGMs, exponential random graphs models; Lutz et al 2019). Researchers are also increasingly using modeling to simulate social transmission of diseases or of information (based on network-based diffusion analysis, Wild and Hoppitt 2018) or to simulate network resilience through targeted deletion (Puga-Gonzalez et al 2018).…”
mentioning
confidence: 99%
“…This cutoff point maximizes the power of the analysis. Also, Grampp et al (2019) observed how social biases influence social learning in juvenile vervet monkeys (Chlorocebus aethiops pygerythrus). Kinship emerged as the most important factor in social attention in juveniles, followed by dominance.…”
mentioning
confidence: 99%